2020
DOI: 10.1186/s12889-020-09616-2
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographics and their impacts on risk factor awareness and beliefs about cancer and screening: results from a cross-sectional study in Newfoundland and Labrador

Abstract: Background Our objective was to examine cancer risk factor awareness and beliefs about cancer treatment, outcomes, and screening, and how these are mediated by sociodemographic variables, among Newfoundland and Labrador residents. Methods Participants aged 35 to 74 were recruited through Facebook advertising, and a self-administered online questionnaire was used to collect data. Descriptive statistics, Spearman rank correlations, and multivariate logistic regression analyses were performed. Results Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 30 publications
2
30
1
Order By: Relevance
“…For example, in the UK, 52% of known risk factors and 36% of cancer myths were accurately identified, compared to 70% of risk factors and 49% of myths in this study [ 19 ]. Variations in the average percentage of correctly identified cancer facts and myths were observed by demographic group, particularly for income, ethnicity, and age, consistent with previous studies [ 19 , 23 , 38 , 39 ]. Differences in beliefs about cancer myths and risk factors by thinking style were observed, suggesting that those who are more actively open-minded and prefer effortful thinking may be better able to identify cancer myths and risk factors, while those who are more close-minded and prefer intuitive thinking are less able.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For example, in the UK, 52% of known risk factors and 36% of cancer myths were accurately identified, compared to 70% of risk factors and 49% of myths in this study [ 19 ]. Variations in the average percentage of correctly identified cancer facts and myths were observed by demographic group, particularly for income, ethnicity, and age, consistent with previous studies [ 19 , 23 , 38 , 39 ]. Differences in beliefs about cancer myths and risk factors by thinking style were observed, suggesting that those who are more actively open-minded and prefer effortful thinking may be better able to identify cancer myths and risk factors, while those who are more close-minded and prefer intuitive thinking are less able.…”
Section: Discussionsupporting
confidence: 89%
“…These findings were consistent with results found in the UK [ 19 ]. However, in Newfoundland and Labrador, being over 70 years of age, drinking more than one unit of alcohol per day, and having a diet low in fibre were the least identified risk factors (≤ 65% correct) [ 23 ]. The results on relatively poor recognition of alcohol use and low fibre diets may not be as surprising as the fact that older age was poorly recognized as a factor; for most cancers, age is the most significant predictor of cancer risk [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the risk factors which the greatest number of participants were aware of included chewing tobacco (90.4%) smoking (88%) second-hand smoking (60%) and environmental pollutions (47.3%). In a study conducted in Canada demonstrated the similar findings in which the majority of participants mentioned that smoking (97.44%) and second-hand smoking (96.55% ) could be risk factor for cancer (Shi et al, 2020).…”
Section: -242supporting
confidence: 59%
“…A previous national study from Palestine found that having a chronic disease was not associated with good awareness of BC risk factors [ 8 ]. Another previous study also demonstrated that participants with no chronic diseases held significantly more positive beliefs about cancer than those with poor/fair health [ 50 ]. These observations are especially important because many previous studies have shown that women with BC were more likely to die from cancer as well as all-cause mortality if they had other comorbidities [ 51 53 ], and that individuals who rated their health as fair or poor were more likely to have barriers to seeking healthcare [ 54 ].…”
Section: Discussionmentioning
confidence: 89%